STUDI LITERATUR : BIMBINGAN KELOMPOK TEKNIK DISKUSI BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Mahmuddah Dewi Edmawati (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
Abstract : This research is a literature study with a descriptive qualitative research type with library research which seeks to describe the role of group guidance on information technology-based discussion techniques in increasing students' learning motivation. In this literature study the author uses various written sources such as articles, journals and documents relevant to the study in this research. This study focuses on the problems of students that occur in the era of the covid-19 pandemic, one of which is the decline in the level of learning motivation. In this case, guidance and counseling services have an important role to help students increase learning motivation so that students can have good self-actualization and optimal learning outcomes. This study aims to determine the role of information technology-based group guidance services to increase student learning motivation through various articles, journals and documents relevant to the study in this study. Group guidance with information technology-based group discussion techniques is able to increase learning motivation, this is because in group guidance there is group dynamics that can increase student learning motivation. Through group guidance activities, all group members conduct discussions, give and receive information, develop communication and interpersonal skills, give each other advice, convey and understand feelings to each other, motivate each other so that group members' learning motivation increases. The implementation of information technology-based group guidance is one of the effective approaches to increase student learning motivation due to the pandemic that does not allow the implementation of face-to-face guidance and counseling activities. Keywords: Group Guidance, Discussion Techniques, and Learning Motivation